Golden balls: A prisoner's dilemma experiment - Donja Darai; Silvia Grätz (University of Zurich, Socioeconomic Institute, 2010)
We analyze cooperative behavior in a prisoner's dilemma game with high stakes, face-to-face communication, and two rounds of pre-play in which the two final contestants are endogenously selected via a voting process. Using data from the British television game show 'Golden Balls', we find a unilateral cooperation rate of 55% and a mutual cooperation rate of 33%. The stake size is on average 13,300 and ranges from 3 to 100,150. Our analysis shows that both stake size and communication have a significant impact on the player's likelihood to cooperate. In particular, we observe a negative correlation between stake size and cooperation. Also certain gestures, as handshakes, decrease the likelihood to cooperate. But, if players mutually promise each other to cooperate and in addition shake hands on it, the cooperation rate increases. We also show that a player's expectation about the stake size matters. Further, we find a strong link between contestant's pre-play behavior and the outcome of the prisoner's dilemma. Players who contribute more to the stake size are less likely to cooperate, even though each player's contribution is determined by a random process. Apart from that, it matters whether a player has lied in the pre-play and whether she experienced her opponent's goodwill. Addressing the partner selection process, we find that contestant's voting decisions are based on objective criteria, i.e., their opponent's monetary contribution to the stake size, as well as subjective personal characteristics, i.e., the opponents' trustworthiness.
Keywords: 330; Gefangenendilemma; Kooperatives Spiel; Theorie